The efficiency consequences of heterogeneous behavioral responses to energy fiscal policies - Sébastien Houde; Joseph E. Aldy (ETH Zurich, CER-ETH - Center of Economic Research, 2017)
The behavioral responses to taxes and subsidies are often subject to various behavioral biases and transaction costs - what we define as "microfrictions". We develop a theoretical framework to show how these microfrictions - and their heterogeneity across the population and policy instruments - affect the design of Pigouvian policies. Standard Pigouvian pricing still holds with transaction costs, but requires adjustment with behavioral biases. We use transaction-level data from the US appliance market to estimate the heterogeneous behavioral responses to an array of energy fiscal policies and to quantify microfrictions. We then assess optimal fiscal policies and find that it is rarely optimal to couple a Pigouvian tax on energy with an investment subsidy in this context. We also find that energy labels - intended to increase the salience of energy information - can interact in perverse ways with both taxes and subsidies.
Keywords: Q4; Q48; Q58; H31; 330; energy fiscal policies; behavioral taxation; demand estimation; durables